The impact of global drug policy on women: shifting the needle - Buxton, Julia (Emerald Publishing, 2021)
The ebook edition of this title is Open Access and freely available to read online. The international strategy of criminalising the cultivation, manufacture, distribution and use of certain psychoactive substances has failed to achieve a 'drug free world'. Examining the impact of drug criminalisation and enforcement on a previously overlooked demographic, this edited collection argues that women are negatively and disproportionately affected by this flawed policy approach. Addressing the lack of attention on the experience of women, this collection details the challenges women face in accessing appropriate treatment and services, the stigmatisation and marginalisation resulting from engagement in illegal drug markets, the violence that women are exposed to, and the punitive sentences imposed on women for drug related offences. Bringing together an international group of academics, advocates, activists and those with lived experience, the editors offer a rounded and realistic view from women's perspectives. In doing so, they facilitate a call for feminist and women's organisations to embrace drug policy reform, and for international and national level drug control authorities to better engage women as stakeholders.